2000
DOI: 10.1017/s1092852900013122
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional Contributions to the CNS Pathophysiology of HIV-1 Infection and Implications for Treatment

Abstract: Nutritional deficiencies are commonplace in patients with human immunodeficiency virus type 1 (HIV-1) infection, and recent research has indicated that nutritional factors may play an important role in the pathogenesis of HIV-1 disease. Although nutritional deficiencies are unlikely to be the primary causative factor in disease progression, they may contribute to cognitive dysfunction, neurologic abnormalities, mood disturbance, and immune dysregulation associated with HIV-1 infection. Furthermore, deficiencie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 124 publications
(97 reference statements)
0
5
0
Order By: Relevance
“…Nutritional deficiencies including micronutrients can be a primary causative factor in HIV disease progression, thereby contributing to cognitive dysfunction. 23 The population in this study, however, was mostly observed to be adequately nourished.…”
Section: Resultsmentioning
confidence: 84%
“…Nutritional deficiencies including micronutrients can be a primary causative factor in HIV disease progression, thereby contributing to cognitive dysfunction. 23 The population in this study, however, was mostly observed to be adequately nourished.…”
Section: Resultsmentioning
confidence: 84%
“…The role of other factors including that of low levels of vitamin B6 reported in HIV-1 infection [52,53] may also contribute to a decrease in CSF 5-HT levels, since vitamin B6 is an important cofactor for the activity of 5-hydroxytryptophan decarboxylase, the enzyme used during the last step in 5-HT synthesis.…”
Section: Discussionmentioning
confidence: 99%
“…Inflammatory disorders are characterized by oxidative stress conditions, which lead to low plasma levels of antioxidants, thus also of vitamins. Nutritional imbalances and deficiencies may contribute to neuropsychiatric disturbances and immune dysregulation associated with HIV-1 infection ( 68 ).…”
Section: Vitamin Status Nutrition and Inflammatory Stressmentioning
confidence: 99%
“…Otherwise, more complex dietary interventions might bear a great potential to increase the clinical benefits of HIV patients. Certainly, nutritional and metabolic parameters play an important role in the pathophysiology of HIV infection and might have therapeutic implications ( 13 , 68 ), which is particularly relevant for individuals suffering from severe nutritional deficiencies ( 80 ). For example, in a study cohort of 504 HIV-infected patients undergoing first ART, low protein nutrition was associated with severity of depression ( 35 ).…”
Section: Vitamin Status Nutrition and Inflammatory Stressmentioning
confidence: 99%